CDK 4/6 inhibitors for the treatment of meningioma - Young, Jacob S.; Kidwell, Reilly L.; Zheng, Allison; Haddad, Alex F.; Aghi, Manish K.; Raleigh, David R.; Schulte, Jessica D.; Butowski, Nicholas A. (Frontiers in Oncology, 2022)
Meningiomas are the most common non-metastatic brain tumors, and although the majority are relatively slow-growing and histologically benign, a subset of meningiomas are aggressive and remain challenging to treat. Despite a standard of care that includes surgical resection and radiotherapy, and recent advances in meningioma molecular grouping, there are no systemic medical options for patients with meningiomas that are resistant to standard interventions. Misactivation of the cell cycle at the level of CDK4/6 is common in high-grade or molecularly aggressive meningiomas, and CDK4/6 has emerged as a potential target for systemic meningioma treatments. In this review, we describe the preclinical evidence for CDK4/6 inhibitors as a treatment for high-grade meningiomas and summarize evolving clinical experience with these agents. Further, we highlight upcoming clinical trials for patients meningiomas, and discuss future directions aimed at optimizing the efficacy of these therapies and selecting patients most likely to benefit from their use.